The effect of shared decision-making on the conflict and regret in menopause symptoms management: an interventional study - Leyla Mortazavi Ghehi; Mohammad Asghari Jafarabadi; Sevil Hakimi; Roghaiyeh Nourizadeh; Esmat Mehrabi; Mahdie Arab Bafrani (BMC Women's Health)
Abstract Introduction Menopausal women often face challenges in choosing appropriate interventions to mitigate distressing menopause symptoms, primarily due to concerns about treatment suitability. Therefore, the present study aimed to assess the effect of shared decision-making (SDM) on conflict and regret in menopause symptoms management. Method This interventional study was conducted on 44 menopausal women aged ≥ 45 years in Tabriz, Iran, from September 2020 to January 2021. Subjects were randomly assigned to the intervention (n = 22), which received SDM-based counseling along with a decision aid (DA) booklet, and control (n = 22) groups. The data were collected using a socio-demographic and obstetric characteristics checklist, awareness of the menopause symptoms management strategies, decisional conflict, and regret. The intergroup differences were compared employing an independent t-test and ANCOVA. Results The mean score of decision conflict [Mean difference (MD): -2.07, 95% CI: -29.65 to -11.92, P = 0.001] and decision regret [MD: -1.25, 95% CI: -1.64 to 0.64, P = 0.03] significantly reduced in the intervention group compared to the control group after the intervention. Additionally, a statistically significant increase in the mean score of women’s awareness was observed in the intervention group compared to the control group following the intervention [(Hormone Therapy: MD: 3.38, 95% CI: 1.01 to 5.57, P = 0.006) (Natural Products: MD: 2.44, 95% CI: 0.93 to 3.94, P = 0.002)]. Conclusion The results indicated the effect of SDM-based counseling on improving women’s awareness of the menopause symptoms management strategies and reducing the decisional conflict and regret.